Análise dinâmica não-linear de sistemas rígido-flexíveis - Machado, Roberto Dalledone (1983)
In the analysis of interaction problems is advantageous to treat each region by implicit or explicit algorithms implemented in the same computational program. The objective of the present work is to study a mixed time integration algorithm applied to non-linear problems. The explicit integration is obtained by the Central Difference Method, while the implicit uses the Newmark Operator. Rigid-flexible systems, as soil-fluid-structures problems, are analysed. In the fluid-structure interaction, the stiffness contribution of fluid domains is disconsidered in order to improve the efficienty of a full implicit algorithm Isoparametric finite elements with variable nodal points are used. Lumped or diagonal mass matrix based in the consistent mass matrix are utilized. Some examples are presented and the results are obtained by implicit, explicit and implicit-explicit analysis.